Work-related traumatic fatal injuries involving confined spaces in Australia, 2000-2012 - Selman, J.; Spickett, Jeffery; Jansz, J.; Mullins, B. (CCH Australia Limited, 2017)
Occupational fatalities remain a significant issue in Australia and worldwide. Confined space fatalities are a particular subset. Confined spaces are defined by a particular set of hazards and often have poor ventilation, which can permit hazardous situations to develop. Confined space fatalities have been investigated in previous international studies; however, no contemporary Australian study specific to work-related confined space fatalities has been undertaken. This study conducted an analysis of work-related traumatic fatal injuries involving confined spaces in Australia based on coronial data. This study aimed to quantify the number of deaths and to provide a detailed description of the personal, industry, nature of the work, and mechanism-specific factors involved. Fifty-nine confined space related deaths were identified over the period 2000-2012; an average rate of 0.05 deaths per 100,000 workers across Australia. This rate is comparable to contemporary US (0.07) and Quebec (0.07) fatality rates.